MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN MENGGUNAKAN MEDIA KARTU ANGKA PADA ANAK USIA 4-5 TAHUN DI TK PEMBINA NEGERI 1 BANGKO KABUPATEN ROKAN HILIR - Raudah, Raudah; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Children's ability to recognize the concept of low numbers, methods and instructional media used by teachers for understanding the introduction of concept numbers for children are still less varied , giving rise to boredom for children. The aim of this study is to make improvements to the learning through appropriate methods to improve the ability to know the concept of numbers , the research method used by is a Class Action Research ( PTK ) with observation techniques, Subjects were children aged 4-5 years at Tk Pembina State 1 Bangko Rokan Hilir number of students as many as 15 people. The results of this study are the media card this figure can increase the ability to know the concept of numbers in children aged 4-5 years in the State of Trustees TK 1 Bangko Rokan Hilir.Keywords: Numbers Concept , Card Numbers